2011
DOI: 10.4067/s0716-10182011000500013
|View full text |Cite
|
Sign up to set email alerts
|

¿Qué fue la plaga de Atenas?

Abstract: In the year 430 B.C., at the beginning of the second year of the Peloponessian War, a terrible epidemic fell upon Athens and the most populous cities in Attica. It would last for just over four years and it would kill 100.000 people, a quarter to a third of the population. We know about it through the masterly description made by Thucydides in his History of the Peloponnesian War. His narrative has withstood twenty fi ve centuries due to its medical interest and, above all, its great dramatic force. The descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Starting from the initial approach, with the first data considered, we now turn to the logistic equation in the following way, (12) Furthermore (7) can also be used so that can be define, b a M = 2 (13) We now proceed to determine the maximum population, considering the new data (Table 2) and the growth rate expressed by evaluating the derivative of the function y 2 (t), to find the solution of (4). The growth ratio with the data in Table 2 With these values, a solution to equation ( 4) is sought, and the system of equations is obtained: With the procedure shown, based on the records provided by the country's authorities, it is found that the epidemic due to the SARS-CoV-2 virus manifests signs of lasting more than 2 years at the national level, with the possibility of around ten million confirmed infections.…”
Section: A More Realistic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from the initial approach, with the first data considered, we now turn to the logistic equation in the following way, (12) Furthermore (7) can also be used so that can be define, b a M = 2 (13) We now proceed to determine the maximum population, considering the new data (Table 2) and the growth rate expressed by evaluating the derivative of the function y 2 (t), to find the solution of (4). The growth ratio with the data in Table 2 With these values, a solution to equation ( 4) is sought, and the system of equations is obtained: With the procedure shown, based on the records provided by the country's authorities, it is found that the epidemic due to the SARS-CoV-2 virus manifests signs of lasting more than 2 years at the national level, with the possibility of around ten million confirmed infections.…”
Section: A More Realistic Modelmentioning
confidence: 99%
“…Thucydides rigorously recounts the desperation of doctors and patients in the face of the devastation of an epidemic for which neither knowledge nor remedies were known in Athens at the time of Pericles, during the Peloponnesian War against the Persians. And especially during the war against Sparta and her allies, in the year 430 before our era [12], [13]. The Antonine plague (165-180 BC) also known as the plague of Galen, because it was this famous doctor who adequately described it, was an epidemic possibly of smallpox or measles that affected the Roman Empire.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of this plague was severe. 4 Roman Empire got decline after it. Modification of religiousness and spirituality were found.…”
Section: Ad; Antonina Plaguementioning
confidence: 99%
“…The disease hit first at Anthon's port. 3,4 The epidemic broke out in May 430 B.C and another wave was seen in summer of 428 B.C and winter of 427-426 B.C. The disease spread from person to person through aerosols/respiratory transmission with a very high attack and spread rate.…”
Section: Introduction 430bc; Plague Of Athensmentioning
confidence: 99%